The Effect of Corporate Governance Mechanism on the Integrity of Financial Statements in Manufacturing Companies in the IDX - Ayu Krisnawati; Justita Dura (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to evaluate whether the mechanism of corporate governance, which involves institutional ownership, management ownership, independent commissioners and audit committee variables, has a significant impact on the integrity of the financial reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. The sampling method uses techniques of non-probability sampling with approach purposive sampling. Based on the research results, it shows that 1) Institutional Ownership has a positive and significant effect on the integrity of financial reports. 2) Managerial ownership has no effect on the integrity of financial reports. 3) Independent Commissioners have a positive and significant influence on the integrity of financial reports. 4) The audit committee has a positive and significant effect on the integrity of financial reports. It is hoped that this research can provide additional strength to integrity in the presentation of financial reports, so that it can support the company's survival.